Struktur Aktansial dan Fungsional Novel Arwāḥ Mut‘abah Karya Asmā’ al-Ḥuwaylī: Perspektif Naratologi A. J. Greimas - Surur, Misbahus; Kumalasari (Al-Ma‘rifah, 2023)
This study aimed to identify and describe the form of actantial structure and functional structure in the novel Arwāḥ Mut‘abah by Asmā’ al-Ḥuwaylī based on the perspective of a French theorist of naratology and semiotics, A. J. Greimas. This research used the descriptive-qualitative research type. The data source in this research is the novel Arwāḥ Mut‘abah by Asmā’ al-Ḥuwaylī with the addition of several references related to theory and objects. Data collection techniques used reading techniques and note-taking (writing) techniques. While the data analysis technique used the Miles and Huberman technique, including data reduction, data display, and verification of data or conclusions. From this research, we found eight actantial schemes. The eight actantial schemes included five perfect schemes and three imperfect schemes. While the functional structure in the novel Arwāḥ Mut‘abah had a complete storyline, namely the initial situation, transformation, and final situation. The final situation in this study is in the form of something that is calming but at the same time tense, namely death.